School of rock [videorecording (Blu-Ray)] - White, Mike, 1970-; Black, Jack, 1969-; Cusack, Joan, 1962-; Silverman, Sarah; Wilkof, Lee; McGregor-Stewart, Kate; Pascal, Adam; Douglass, Suzzanne, 1957-; Gaydos, Joey, Jr., 1991-; Cosgrove, Miranda, 1993-; Clark, Kevin, 1988-; Tsai, Robert; et al. (Paramount, 2012)
When his band votes him out due to his embarrasing musical antics, Dewey has to make the rent somehow. After intercepting a call for his substitute-teacher roomie Ned, Dewey finds himself in front of a class of elite elementary school students. Dewey decides to take on the music program and makes it his goal to teach them the gospel of rock and roll. His ulterior motive is to get them to compete against his former band for a cash prize.